ANALYSIS OF EDUCATION AND SOCIETY OF VIJAYNAGAR EMPIRE - Suman, Anshuman (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The education system in Vijayanagara was not materially different from the ancient Indian education system . Education was not directly encouraged, but temples, monasteries, Agragahs, etc. were the main centers of education.1 Primary schools or pathshalas were attached to temples and elementary education was provided there.2 Pathshalas were run in temples for education. Children were taught in their mother tongue. There was a system of higher education in Sanskrit Girls were also educated. Thousands of students pursued higher education in Madurai.